Diseño de estrategia de distribución para la serie documental “Moderna Contemporánea / Cali Sobre el Papel” (2019)
The advance of technology has been reduced in the daily life of the human being, the way to appreciate the different audiovisual products, because not exist a manual that specifies the form of exhibition a product should reach the public This document explores the different distribution windows that can be seen for an audiovisual realization, with the aim of finally creating an exhibition route of the documentary series "Modern Contemporary / Cali on Paper" taking into account its format